(Nota n.º 3) Nematódeos da aboboreira - Lordello, Luiz Gonzaga E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
In the State of S. Paulo, Brazil, squash plants (Cucurbita spp.) are attacked by the Javanese nematode (Meloidogyne javanica) and by M. incognita acrita. Squash belongs to that group of plants in which the root-knot nematodes break through the root surface, so that the egg-producing females protrude from the root, showing yellowish or brow nish egg masses attached to them. Washed roots show numerous small dark spots, each corresponding to an ootheca, which is adhering to a mature female. A curious abnormal female of M. i. acrita was obtained from a sample of squash roots. This female's body showed two globular parts, separated by a deep constriction. The convoluted ovaries were found to fill both portions of the body.